Regulation of Cigarette Use According to International Law and Indonesian National Law - Prayitno, Rangga; Miekhel, J. Sam (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2023)
Health is a human right that must be protected by the state. The right to live healthy is a basic right that must be guaranteed because health is part of the primary needs of every human being. Smoking is very dangerous for health. The use of cigarettes has an impact on the health of other people around the smoker. This action violates a person's right to a healthy environment as guaranteed by the constitution. This research uses normative juridical research methods. The results found in this study are: (1) Regulation of the use of cigarettes according to international law is contained in the FCTC. (2) The Indonesian government has established a Draft Law on Tobacco and Government Regulations as a response to regulation of the use of cigarettes internationally (3) Regulations in Indonesia regarding tobacco control are currently in the form of Government Regulations, including Government Regulation No. 19 of 2003 concerning Tobacco Control.